A GABAergic Dysfunction in the Olivary–Cerebellar–Brainstem Network May Cause Eye Oscillations and Body Tremor. II. Model Simulations of Saccadic Eye Oscillations - Optican, Lance M.; Pretegiani, Elena (Frontiers in Neurology, 2017)
Eye and body oscillations are shared features of several neurological diseases, yet their pathophysiology remains unclear. Recently we published a report on two tennis players with a novel presentation of eye and body oscillations following self-administration of performance-enhancing substances. Opsoclonus/flutter and limb tremor were diagnosed in both patients. Common causes of opsoclonus/flutter were excluded. High-resolution eye movement recordings from one patient showed novel spindle-shaped, asymmetric saccadic oscillations (at ~3.6 Hz) and ocular tremor (~40-60 Hz). Based on these findings we proposed that the oscillations are the result of increased GABAA receptor sensitivity in a circuit involving the cerebellum (vermis and fastigial nuclei), the inferior olives and the brain stem saccade pre-motor neurons (excitatory and inhibitory burst neurons, and omnipause neurons). We present a mathematical model of the saccadic system, showing that the proposed dysfunction in the network can reproduce the types of saccadic oscillations seen in these patients.